2020
DOI: 10.1097/jxx.0000000000000357
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory descriptive study of compassion fatigue and compassion satisfaction: Examining potential risk and protective factors in advanced nurse practitioners

Abstract: Background: Larger patient caseloads and increased workplace responsibility for nurse practitioners (NPs) may exacerbate factors leading to compassion fatigue (CF). Purpose: The purpose of this study is to analyze the rate of burnout in practicing NPs by looking at contributing factors that play a role in CF and compassion satisfaction (CS). Methods: A NP social media platform was used to distribute a survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Older participants had better CS scores (aged 50–60, 60.4%; aged >60, 58.3%); high levels of CS were also found in those with 5–10 years in practice (58.8%), with the highest CS scores reported by those with >20 years in practice (80%). 17 In another study, older nurses and those with more time in the role (16–20 years) had higher job satisfaction scores, decreased stress and lower levels of burn-out, while all age groups below 60 years+had lower job satisfaction scores, and nurses in mid-life (31–40 years old) had higher DP scores than older nurses (51–60 years old). 7 A third study found that while 41% of participants had never experienced burn-out, the highest rates of burn-out were reported in the 24–34 years (former burn-out 32.6%; current burn-out 30.7%), and 35–44 years (former 41.0%; current 29.8%) age groups.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Older participants had better CS scores (aged 50–60, 60.4%; aged >60, 58.3%); high levels of CS were also found in those with 5–10 years in practice (58.8%), with the highest CS scores reported by those with >20 years in practice (80%). 17 In another study, older nurses and those with more time in the role (16–20 years) had higher job satisfaction scores, decreased stress and lower levels of burn-out, while all age groups below 60 years+had lower job satisfaction scores, and nurses in mid-life (31–40 years old) had higher DP scores than older nurses (51–60 years old). 7 A third study found that while 41% of participants had never experienced burn-out, the highest rates of burn-out were reported in the 24–34 years (former burn-out 32.6%; current burn-out 30.7%), and 35–44 years (former 41.0%; current 29.8%) age groups.…”
Section: Resultsmentioning
confidence: 94%
“…Finally, an exploration of CF and CS, both known precursors to burn-out, reported low levels of CF and high levels of CS in the sample (n=208), deducing low levels of burn-out across the cohort. 17 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations